Improving Learning Outcomes in Short-Distance Running Through a Play-Based Approach for Grade V Students - Aji, Bayu Purnomo; Wismanadi, Himawan (TEGAR: Journal of Teaching Physical Education in Elementary School, 2023)
Sprinting requires one aspect of fitness, namely speed, which serves to support the body's ability to perform the same and repeated movements in a short time. This study aims to determine the level of effectiveness in improving the learning outcomes of 30-meter short-distance running using a play-based approach. The method used is action research, conducted in two cycles. The subjects of this study were 35 fifth-grade students from SD Negeri Manukan Wetan IV Surabaya, consisting of 13 boys and 22 girls. The study utilized pre-test and post-test data collection techniques. Before the implementation of action research, the students had an average completion score of 36 for short-distance running. This score increased to 45.71 in cycle I. In cycle II, the initial student score of 58.29 improved to 90.29, with 4 students failing to complete the test. Therefore, it can be concluded that the play-based approach has proven effective in enhancing the learning outcomes of 30-meter short-distance running for fifth-grade students at SD Negeri Manukan Wetan IV Surabaya for the 2022/2023 school year.